Den lille galskab: Symboliseringspraksis som en psykodynamisk metode til samspil med den ubevidste psyke. - Gitz-Johansen, Thomas (Psyke & Logos, 2016)
The article discusses symbolization as a specific psychological method informed by psychodynamic theory. The point of departure is taken in a critique of modern society as disenchanted in the sense that a one-sided appreciation of reason has displaced and delegitimized irrational modes of consciousness. This process has led to great technological, scientific and administrative advantages, but it has also weakened the connection between consciousness and the unconscious layers of the psyche. Utilizing psychodynamic theory, it is argued that the connection between consciousness and the unconscious can be strengthened through what is called practices of symbolization. Three such practices are discussed: Symbolic play, active imagination, and religious symbolic practices. Two pitfalls of symbolization are then discussed: Escapism and ‘symbolic equation’ or the confusion of symbol and reality. Finally, the article discusses practices of symbolization in a broader cultural context.